2019
DOI: 10.1029/2019gl082723
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dynamic Stress Cycling on the Compressive Strength of Rocks

Abstract: Quasi‐static rock strength is a nonconservative property, as fatigue during cyclic loading reduces the macroscopic strength. When strain rate under compressive loading increases above a lithology‐specific threshold, the primary failure mechanism transitions from localized failure along discrete fractures to distributed fracturing. However, the role of load path under high strain rate conditions has not been explored in any detail. We examine the effect of rapid stress cycles on the dynamic compressive strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 49 publications
(123 reference statements)
1
20
0
Order By: Relevance
“…Barber and Griffith (2017) have shown in weakly confined dynamic compression experiments that Arkansas Novaculite produces ∼86 times more surface area per unit mass (∼6.0 m 2 g −1 ) than Westerly Granite (∼0.07 m 2 g −1 ), highlighting the important role played by material properties and microstructure. Several experimental studies have shown that rapid dynamic stress cycling reduces dynamic strength and more easily leads to intense fragmentation (Badge & Petroš, 2005; Braunagel & Griffith, 2019; X. Li et al., 2021; Liu & Zhao, 2021). Additionally, material contrast across a fault may strongly amplify dynamic effects (e.g., Ben‐Zion & Rice, 1997; Rice & Ben‐Zion, 1996; Shi et al., 2008; Shlomai et al., 2021; Shlomai, Kammer, et al., 2020; Thomas et al., 2017), and the background stress orientation can markedly influence the spatial scale of the damage zone (Xu et al., 2012a, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Barber and Griffith (2017) have shown in weakly confined dynamic compression experiments that Arkansas Novaculite produces ∼86 times more surface area per unit mass (∼6.0 m 2 g −1 ) than Westerly Granite (∼0.07 m 2 g −1 ), highlighting the important role played by material properties and microstructure. Several experimental studies have shown that rapid dynamic stress cycling reduces dynamic strength and more easily leads to intense fragmentation (Badge & Petroš, 2005; Braunagel & Griffith, 2019; X. Li et al., 2021; Liu & Zhao, 2021). Additionally, material contrast across a fault may strongly amplify dynamic effects (e.g., Ben‐Zion & Rice, 1997; Rice & Ben‐Zion, 1996; Shi et al., 2008; Shlomai et al., 2021; Shlomai, Kammer, et al., 2020; Thomas et al., 2017), and the background stress orientation can markedly influence the spatial scale of the damage zone (Xu et al., 2012a, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…As the rock tensile strength ( T O ) is low (∼1–10 MPa) for sedimentary rocks near the surface, it is conceivable that supralithostatic overpressure (i.e., P f = σ 3 + T O ) under the condition ( σ 1 − σ 3 )/ T O < 4 results in extension fractures, forming sub‐horizontal extension veins perpendicular to σ 3 (Figure 1 of Sibson, 2017). It is conceivable that, during the great earthquakes, rapid cyclic dynamic stresses from strong ground motions may compromise the rock strength (Bagde & Petros, 2005; Braunagel & Griffith, 2019; Erarslan & Williams, 2012), facilitating new horizontal extensional veins near the surface in the Sumatra forearc (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Ping et al [ 18 ] carried out impact compression tests on coal-mine sandstone samples under different loading rates, and the analysis showed that the dynamic compressive strength, dynamic elastic modulus, and strain rate of sandstone were positively correlated with the incident energy. Braunagel et al [ 19 ] used an improved split-Hopkinson compression bar to study the effect of cyclic-impact loads on the dynamic compressive strength of westerly granite. The dynamic strength and deformation characteristics of rock under impact loading can be comprehensively described using a dynamic constitutive model.…”
Section: Introductionmentioning
confidence: 99%